ChemInform Abstract: Crystal Structure of 3R‐LiTiS2 and Its Stability Compared to Other Polymorphs. Issue 8 (25th February 2014) - Nakhal, Suliman; Lerch, Martin; Koopman, Jeroen; Islam, Mazharul M.; Bredow, Thomas
Abstract 3R‐LiTiS2 is prepared by heating a stoichiometric mixture of Ti, S, and Li2S (evacuated silica tubes, 800 °C, 2 weeks) with 10% of Li1+xTi2‐xO4 and TiO2 as byproducts followed by reheating in H2S (alumina crucible, 750 °C, 4 h).